Determinants and performance mapping of income inequality before and during pandemic Covid-19 in Sumatra, Indonesia - Arif Rahman; Sukma Hayati Hakim; Nurmala Fitri (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to examine the determinants of income inequality and to map the performance of each province based on the interaction among variables before and during the Covid-19 pandemic. It employs panel data regression analysis and applies the IPA quadrant method for two observation periods, 2015-2019 and 2020-2022. Data were sourced from the Central Bureau of Statistics and the Ministry of Environment. The findings suggest that improvements in democracy, environmental quality, and real GRDP per capita can help reduce income inequality, whereas the industrial sector appears to exacerbate it. Real output per capita exerts the strongest influence in reducing inequality. The quadrant analysis results show that Aceh Province experienced worsening inequality performance compared to the pre-pandemic period, while inequality in other provinces has generally stabilised. No high-income province was found to have low inequality status. Democracy performance across Sumatera Island was more volatile. In the industrial sector, only North Sumatra recorded weaker performance. Careful fiscal, monetary, and microeconomic policy consideration are thus required, especially regarding real output per capita growth and industrial sector expansion to prevent further widening of the income gap.